ANALISIS KOMPARASI KEBIJAKAN PERPAJAKAN TRANSAKSI E-COMMERCE YANG BERLAKU DI INDONESIA DENGAN NEGARA LAIN (UNI EROPA, AUSTRALIA, KOREA SELATAN, INDIA, TIONGKOK, AMERIKA SERIKAT, DAN JEPANG) - Muhammad Rheza Ramadhan; Anindya Fauziyah Basuki (DAS Institute, 2021)
Indonesia has experienced an increase in users of e-commerce platforms, resulting in increased income for sellers, both individuals and entities, who conduct online sales transactions. Therefore, the Indonesian government sets a tax policy for online sellers. However, the Indonesian government still has several obstacles, one of which is that e-commerce transactions have an eternal nature. To answer these problems, the author compares the taxation policies on e-commerce transactions that apply in Indonesia with the tax policies on e-commerce transactions that apply in other countries, namely the European Union, Australia, South Korea, India, China, the United States, and Japan. The writing method used by the author is a literature study method. This paper shows that the taxation policy on e-commerce transactions in Indonesia, the European Union, Australia, South Korea, India, China, the United States, and Japan imposes a Value Added Tax (VAT) or the like as a consumption tax on goods. And services as well as sales tax and Income Tax. In addition, several countries have created platforms or special teams to manage taxes from e-commerce transactions, namely the platform Mini One Stop Shop (MOSS), now called OSS (European Union); Korean Fair Trade Commission (KFTC) (South Korea); Professional Team for E-Commerce Taxation (Protect) (Japan). Therefore, Indonesia needs to follow the example of the European Union, South Korea, and Japan in terms of establishing a system or team dedicated to managing tax collection from e-commerce transactions